Incomplete Resolution of Deep Vein Thromboses during Rivaroxaban Therapy - Jonathan M. Yaghoubian; Jacob Adashek; Bahareh Yaghoubian-Yazi; Menachem Nagar; Nojan Toomari; Richard J. Pietras; Uri M. Ben-Zur (Case Reports in Cardiology)
We present the case of a patient with a deep vein thrombosis (DVT) who failed rivaroxaban therapy. Our patient initially presented with left lower extremity edema, erythema, and pain. He was subsequently started on rivaroxaban therapy for a combined treatment period of 12 months, during and after which he persisted to have evidence of a DVT. The patient’s prescribed drug regimen was changed from rivaroxaban to warfarin, which demonstrated a rapid resolution of the DVTs as determined by ultrasound assessment of our patient’s lower extremity veins. Rivaroxaban, a factor Xa inhibitor, is a well-known oral anticoagulant that is used for a variety of indications and has become a mainstay in the treatment of deep vein thrombosis. With the introduction and emergence of this medication in the clinic, postmarketing reports of efficacy or lack thereof are important to review. In conclusion, we anticipate that it is likely that there are other patients with DVTs who may not respond to rivaroxaban and for whom alternative anticoagulation therapies should be explored.